2022
DOI: 10.1186/s13063-022-06255-3
|View full text |Cite|
|
Sign up to set email alerts
|

Study protocol for pragmatic trials of Internet-delivered guided and unguided cognitive behavior therapy for treating depression and anxiety in university students of two Latin American countries: the Yo Puedo Sentirme Bien study

Abstract: Background Major depressive disorder (MDD) and generalized anxiety disorder (GAD) are highly prevalent among university students and predict impaired college performance and later life role functioning. Yet most students do not receive treatment, especially in low-middle-income countries (LMICs). We aim to evaluate the effects of expanding treatment using scalable and inexpensive Internet-delivered transdiagnostic cognitive behavioral therapy (iCBT) among college students with symptoms of MDD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 99 publications
(139 reference statements)
1
2
0
Order By: Relevance
“…Consistent with previous research (Cuijpers et al, 2019; J. H. Wright et al, 2019), our preregistered hypothesis (Benjet et al, 2022) was that participants randomized to guided i-CBT would have significantly better aggregate outcomes than those randomized to self-guided i-CBT. This has been found not only for remission but also for symptoms of clinical depression (Berger et al, 2011; Cuijpers et al, 2019) and anxiety disorders (Ciuca et al, 2018; Oliveira et al, 2023).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Consistent with previous research (Cuijpers et al, 2019; J. H. Wright et al, 2019), our preregistered hypothesis (Benjet et al, 2022) was that participants randomized to guided i-CBT would have significantly better aggregate outcomes than those randomized to self-guided i-CBT. This has been found not only for remission but also for symptoms of clinical depression (Berger et al, 2011; Cuijpers et al, 2019) and anxiety disorders (Ciuca et al, 2018; Oliveira et al, 2023).…”
supporting
confidence: 84%
“…As discussed in more detail elsewhere (Luedtke et al, 2019) and in our preregistered protocol (Benjet et al, 2022; https://ClinicalTrials .gov, Identifier NCT04780542), we used simulation to estimate the required sample size for 0.8 power to detect heterogeneity of treatment effects (the ultimate focus of this research) that would result in a 5% higher aggregate remission rate if all participants were optimized across interventions rather than randomized across interventions. This required sample size was approximately 500 participants per intervention arm initiating treatment based on an assumption of mildly informative loss to follow-up comparable in magnitude to the loss rates found in previous i-CBT trials (Torous et al, 2020).…”
Section: Power Analysismentioning
confidence: 99%
“…Initial follow-up SAQ nonrespondents were sent email reminders, WhatsApp or Telegram messages, and telephone calls to minimize loss to follow-up (eMethods in Supplement 2). More details on the study design are reported elsewhere . Initial data analysis for the present report was conducted from May 23 to October 26, 2022.…”
Section: Methodsmentioning
confidence: 99%
“…El primero de ellos, el estudio "Yo puedo sentirme bien" (Benjet et al, 2022), busca evaluar los efectos de un tratamiento transdiagnóstico Cognitivo Conductual realizado a través de Internet (iCBT, por su sigla en inglés) para tratar Trastorno de Depresión Mayor y cia y a la cultura afectan el avance en la personalización de tratamientos psicoterapéuticos. A continuación, se mencionarán dos grandes áreas que se vinculan y retroalimentan entre sí, generando obstáculos o desafíos a la hora de implementar estrategias para personalizar tratamientos.…”
Section: ¿Cuál Es El Estado De La Investigación Sobre Personalización...unclassified